1982
DOI: 10.1029/jb087ib07p05351
|View full text |Cite
|
Sign up to set email alerts
|

Paleothermometry of the Sydney Basin

Abstract: Evidence from overprinting of magnetizations of Late Permian and Mesozoic rocks and from the rank of Permian coals and Mesozoic phytoclasts (coal particles) suggests that surface rocks in the Sydney Basin, eastern Australia, have been raised to temperatures of the order of 200°C or higher. As vitrinite reflectance, an index of coal rank or coalification, is postulated to vary predictably with temperature and time, estimates of the paleotemperatures in the Sydney Basin based on observed vitrinite reflectance me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
72
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(78 citation statements)
references
References 23 publications
6
72
0
Order By: Relevance
“…(8) Substituting MIDDLETON and SCHMIDT'S (1982) constants into equation (7) we have logR=0.0289T+0.182logt-1.01.…”
Section: Discussionmentioning
confidence: 99%
“…(8) Substituting MIDDLETON and SCHMIDT'S (1982) constants into equation (7) we have logR=0.0289T+0.182logt-1.01.…”
Section: Discussionmentioning
confidence: 99%
“…Some investigations of VRM (e.g., Kent, 1985;Smith and Verosub, 1994) have also assessed the VRM theory of Walton (1980) and Middleton and Schmidt (1982), which attempts to modify Equation (4) slightly to account for the effect of grainsize distributions. It is has been found that this model appears to work better than Equation (4) for long timescales, i.e, >>1 Myrs, but for shorter timescales, i.e., thousands of years, Equation (4) appears to be more applicable (Smith and Verosub, 1994).…”
Section: Figure 1 | a Schematic Of Vrm Acquisition (A)mentioning
confidence: 99%
“…We also considered the VRM theory of Walton (1980) and Middleton and Schmidt (1982), which requires the same input data as Equation (4), though it is slightly modified. When we applied this approach to our data, all the ages for the erratics were less than a year.…”
Section: Comparisons With Previous Studiesmentioning
confidence: 99%
“…The Sydney Basin formation process consisted of a foreland-basin deposition component-a result of tectonic loading (the syn-orogenic phase), and a basin response to thrust-belt erosion (post-orogenic phase) (Heller et al 1988). The Sydney Basin is located between the New England and Lachlan Fold belts and consists of Permian-Triassic sedimentary sequence of at least 4 km thick (Middleton and Schmidt 1982). At its thickest point, the Sydney Basin is cross-cut by the northeasterly dipping frontal thrust fault of the Tamworth Arc of the New England Fold belt, and gradually thins towards the south (Conaghan et al 1982).…”
Section: Geological Backgroundmentioning
confidence: 99%